Bio-Hand Sanitizer Based on Peel of Lime (Citrus aurantifolia S) and Leaves Betel (Piper betle L) - Nila Tanyela Berghuis; Kumara Dimas Setiawan; Angelica Maratu; Pusfianty Pusfianty; Tasya Amanda; Roehanul Janah; Revita Sari (Chimica et Natura Acta, 2023)
The large number of antiseptic products on the market provide choices for people to choose alcoholic or non-alcoholic hand sanitizers. Most commercial hand sanitizers are 70% to 90% alcohol-based. For some people, the use of alcohol-based hand sanitizers is not friendly for sensitive skin. Therefore, in this study efforts were made to minimize the use of alcohol as an antiseptic agent in hand sanitizers by using lime peel extract and betel leaf extract. Betel leaves contain chemicals that are useful as antiseptic, antibacterial, and antioxidant substances. The lime peel contains flavonoid compounds that are useful as antioxidants, antiseptics, anticancer, anti-inflammatory, and antibacterial. The results showed that the extraction of lime peel was dark brown and betel leaves were blackish brown. Lime peel extraction was carried out for 5 hours using the maceration method while lime peel extraction used the reflux method. The results of the inhibition test using the Disk Diffusion Test method showed that the growth of bacteria in the sample area grew less compared to the eco-enzyme and water. While the results of the organoleptic test showed that bio-hand sanitizer products made from the lime peel and betel leaf were quite attractive to respondents.